2020
DOI: 10.2106/jbjs.19.01354
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Open Versus Endoscopic Carpal Tunnel Release

Abstract: Background: Carpal tunnel syndrome is the most common upper-extremity nerve compression syndrome. Over 500,000 carpal tunnel release (CTR) procedures are performed in the U.S. yearly. We estimated the cost-effectiveness of endoscopic CTR (ECTR) versus open CTR (OCTR) using data from published meta-analyses comparing outcomes for ECTR and OCTR. Methods: We developed a Markov model to examine the cost-effectiveness of OCTR versus ECTR for patients undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The exact difference in procedural time is likely irrelevant and would not affect cost-effectiveness studies in a significant manner. 34…”
Section: Surgical Timementioning
confidence: 99%
See 2 more Smart Citations
“…The exact difference in procedural time is likely irrelevant and would not affect cost-effectiveness studies in a significant manner. 34…”
Section: Surgical Timementioning
confidence: 99%
“…With the assumption that patients undergoing ECTR were able to return to work 8.21 days earlier than those undergoing OCTR, they found that ECTR was actually more cost-effective than OCTR from the societal perspective. 34 ECTR was also more cost-effective from the payor perspective when using a willingness-to-pay threshold of $100,000/quality-adjusted life year, a common threshold used in healthcare cost-effectiveness studies. 34,35 Specifically, ECTR in the office setting is the most cost-effective measure, followed by ECTR in the operating room, OCTR in the office setting, and OCTR in the operating room.…”
Section: Endoscopic Versus Open Carpal Tunnel Releasementioning
confidence: 99%
See 1 more Smart Citation
“…7,8 In addition to the open procedure, minimally invasive methods with small incisions and endoscopic surgery have been developed to lessen these sequels, specifically pillar pain and scar discomfort. [8][9][10] Recently the ultrasound-guided looped thread carpal tunnel release (TCTR) technique has been introduced that provides the nerve decompensation by running the thread under and over the TCL followed by oscillating the thread in the distal direction and severing the TCL indirectly. 11,12 This study was designed and performed to present a novel approach to cutting TCL by the thread looping technique without the use of ultrasonography.…”
mentioning
confidence: 99%
“…1 Carpal tunnel release is one of the most common procedures of the upper extremity in the United States, with greater than 500,000 cases completed annually. 2 It is either performed as either an open CTR (OCTR) or endoscopic CTR (ECTR) procedure. However, there is no consensus on superiority of the 2 approaches.…”
mentioning
confidence: 99%